IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY PROTOCOLS IN HOSPITALITY DURING COVID-19 - Hardy, I Putu Dedy Kastama; Wirawan, I Made Ady (LPPM Universitas Jambi, 2026)
The COVID-19 pandemic severely disrupted the global hospitality industry, causing widespread declines in occupancy rates, revenue, and workforce stability. Despite growing awareness of occupational health and safety (OHS), there remains a critical knowledge gap regarding the effectiveness of OHS protocol implementation in supporting hospitality sector recovery. This study aimed to evaluate and synthesize evidence on OHS protocol implementation strategies in the hospitality sector during the COVID-19 pandemic. Methods: A systematic literature review combined with meta-analysis was conducted following PRISMA guidelines. Five peer-reviewed studies published from 2020 to 2025 were analyzed using PICOS-based inclusion and exclusion criteria. Data were extracted and synthesized thematically; effect sizes and confidence intervals were estimated through a visual meta-analysis using a bar chart and forest plot. Results: The sustainable tourism governance model demonstrated the highest relevance level (90%), followed by safety policy implementation (85%) and the Perception-Reaction-Prediction (PRP) model (80%). Urban hotels adopted health protocols more rapidly than rural hotels, and women demanded stricter safety standards than men. All five reviewed studies reported significant effect sizes with confidence intervals that did not cross zero. Discussion/Novelty: This study makes a novel contribution by providing the first systematic meta-analytic synthesis of OHS protocol effectiveness specifically within the hospitality sector during a pandemic context, integrating governance, demographic, and geographic dimensions.